Pengembangan Ekonomi Kreatif pada Pedagang Suku Jawa - Lisa Nursita; Nur Hidayanti; Muh Givary Suriyono (Ideas: Jurnal Pendidikan, Sosial dan Budaya, 2022)
Creative economy is human creativity in developing its business. The creative economy needs to be developed by traders, entrepreneurs or business people with the understanding and assistance of human resource skills, technology and the quality of the products being marketed. The purpose of this study is to determine the extent to which Javanese traders understand the creative economy and how they develop their businesses through implemented innovations. The research method used is qualitative research with a phenomenological study. The results of the study found that Javanese traders understand and apply the concept of the creative economy, and are very concerned about product quality. According to them, the level of entrepreneurship education and training does not really affect the success of the business, but it depends on the experience of entrepreneurship. They also use technology for marketing. Innovative human resource and business skills greatly assist them in increasing consumers' purchasing power. Trading businesses must always be innovative because of market competition that must be anticipated.